Security and victimization of university students in the city of Oporto - Nunes, Laura M. (2018)
An exploratory study with 307 students from higher education institutions in Porto is presented. Participants of both sexes, aged 18-48 (M=23; SD=5.6), responded to a local security diagnostic questionnaire in order to capture perceptions of crime and victimization in the area, the feelings of security and the conceptions about the police action. The results point to a general perception of security, despite reported robbery or panhandle. The experience of victimization (15%), not always reported to the authorities, translated into a weakened perception as to the police action. The study concludes by the importance of the strategic formulation of security plans based on community participation.